The chemical composition and fluxes of atmospheric wet deposition at four sites in South Africa. (December 2016) - Conradie, E.H.; Van Zyl, P.G.; Pienaar, J.J.; Beukes, J.P.; Galy-Lacaux, C.; Venter, A.D.; Mkhatshwa, G.V.
Abstract: South Africa is the economic hub of southern Africa and is regarded as an important source region of atmospheric pollutants. A nitrogen dioxide (NO2 ) hotspot is clearly visible from space over the South African Mpumalanga Highveld, while South Africa is also regarded as the 9th largest anthropogenic sulphur (S) emitting country. Notwithstanding the importance of South Africa with regard to nitrogen (N) and S emissions, very limited data has been published on the chemical composition of wet deposition for this region. This paper presents the concentrations of sodium (Na + ), ammonium (NH4 + ), potassium (K + ), calcium (Ca 2+ ), magnesium (Mg 2+ ), nitrate (NO3 − ), chloride (Cl − ), sulphate (SO4 2− ) and water-soluble organic acids (OA) in the wet deposition samples collected between 2009 and 2014 at four South African IDAF (IGAC DEBITS Africa) sites, which are regarded as regional representatives of the north-eastern interior. Also, wet deposition fluxes of the ten ions are calculated and presented in this paper. The results show that the total ionic concentrations and fluxes of wet deposition were much higher at the two sites closer to anthropogenic emissions, while the pH of wet deposition at these two sites were lower compared to that of the two sites that were less impacted by anthropogenic emissions. . The major sources of the ten ions included marine, terrigenous (crust), fossil fuel combustion, agriculture and biomass burning. Significant contributions from fossil fuel combustion were determined for the two sites in close proximity to anthropogenic source regions. The results of back trajectory analysis, however, did indicate that the two remote sites are also affected by air masses passing over the source region through anti-cyclonic recirculation. The largest contributions at the two sites distant from the anthropogenic source regions were marine sources, while the impact of biomass burning was also more significant at the remote sites. Comparison to previous wet deposition measurements at the South African IDAF sites indicated increases in the wet deposition fluxes of S and N, and more wet deposition events with lower pH. This could be ascribed to a significant increase in anthropogenic activities and population growth in this part of South Africa with an associated increase in energy demand. Highlights: Significant impacts of anthropogenic activities on rain chemistry are indicated. Contributions from marine and crustal sources are reflected in rain chemistry. More rainfall events with low pH occur at sites nearby anthropogenic sources. Increased S- and N-deposition, and rain events with lower pH from 1984 to 2014. Rainfall chemistry reflects increased anthropogenic sources and population growth.